2007
DOI: 10.1002/ejoc.200700206
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Concave Imidazolinium Salts as Precursors to Chiral Concave N‐Heterocyclic Carbenes

Abstract: Imidazolinium moieties have been incorporated into bimacrocycles to generate precursors for concave N‐heterocyclic carbenes (NHCs). By using one symmetrically substituted benzene bridgehead and one naphthalene bridgehead devoid of local C2‐symmetry, axially chiral concave imidazolinium ions have been obtained. Starting from 2,7‐dihydroxy‐1‐nitronaphthalene (7), the phenol groups have been transformed to 4‐pentenyl ethers 8, and the nitro group was then reduced to the corresponding amine 9. Next, 9 and a 2,6‐bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…We showed that in case of the 4,5-nonsubstituted chiral imidazolinium salt 10, the use of enantiopure Λ-BINPHAT (20) as a counterion led to NMR spectra with two sets of signals with different intensities. [25] The rational is that one enantiomeric imidazolium ion interacts more strongly with the chiral counterion than the other and is stabilized by this ion pair formation. Noteworthy is that the amplification of one species can only happen by rotation along the N-C Ar bonds (Scheme 1) and only if the energy of the rotation barrier is low.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We showed that in case of the 4,5-nonsubstituted chiral imidazolinium salt 10, the use of enantiopure Λ-BINPHAT (20) as a counterion led to NMR spectra with two sets of signals with different intensities. [25] The rational is that one enantiomeric imidazolium ion interacts more strongly with the chiral counterion than the other and is stabilized by this ion pair formation. Noteworthy is that the amplification of one species can only happen by rotation along the N-C Ar bonds (Scheme 1) and only if the energy of the rotation barrier is low.…”
Section: Resultsmentioning
confidence: 99%
“…In solution, the molecules are flexible, and 10 inverts to its enantiomer quickly. [25] For investigation of the configurational stability of new dimethylated axially chiral concave bimacrocycle 19, two NMR experiments were carried out: First, racemic imidazolinium chloride 19 was converted into a diastereomeric salt with enantiopure Λ-BINPHAT [27] ( Figure 5). We showed that in case of the 4,5-nonsubstituted chiral imidazolinium salt 10, the use of enantiopure Λ-BINPHAT (20) as a counterion led to NMR spectra with two sets of signals with different intensities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations